2020
DOI: 10.3389/fonc.2020.00991
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Oxidative Phosphorylation Reverses Bone Marrow Hypoxia Visualized in Imageable Syngeneic B-ALL Mouse Model

Abstract: Rytelewski et al. OxPhos and BALL Marrow Hypoxia intense oxidative phosphorylation (OxPhos) leading to the onset of metabolic BM hypoxia despite increased BM vascularization. Targeting mitochondrial respiration may be a novel approach to counteract BM hypoxia in BALL and, possibly, tumor hypoxia in other OxPhos-reliant malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Recent studies showed that CD39 expression was not induced by IFN-γ [ 59 , 60 ] whereas it can be induced under hypoxic conditions [ 61 , 62 ]. ETCI inhibitors have already been reported to interfere with HIF stabilization such as IACS [ 15 , 63 ] and metformin [ 64 , 65 , 66 ]. EVT-701 was also developed from a screening campaign to characterize HIF-1α inhibitors [ 22 ]; therefore, we propose an impairment of hypoxic signaling by interfering with HIF-1α stabilization as the mechanism by which EVT-701 decreases CD39 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that CD39 expression was not induced by IFN-γ [ 59 , 60 ] whereas it can be induced under hypoxic conditions [ 61 , 62 ]. ETCI inhibitors have already been reported to interfere with HIF stabilization such as IACS [ 15 , 63 ] and metformin [ 64 , 65 , 66 ]. EVT-701 was also developed from a screening campaign to characterize HIF-1α inhibitors [ 22 ]; therefore, we propose an impairment of hypoxic signaling by interfering with HIF-1α stabilization as the mechanism by which EVT-701 decreases CD39 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst others, alterations in IKZF1, TP53-, CDKN2A, CREBBP, NR3C2, MSH6, PRPS1, PRPS2, NT5C2 are ETV6 are associated with unfavorable outcome and/or therapy resistance in B-ALL [400][401][402][403]. Regarding mitochondrial biogenesis in B-ALL, a recent pre-clinical data showed high oxygen consumption, which can be a future therapeutic target in therapy-resistant B-ALL [404].…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%
“…Vascular remodeling is a feature of leukemia progression. It has been shown in a murine model of BCR-ABL1 B-ALL that during leukemia progression, there is an increase in blood vessel density and therefore a higher oxygen supply ( 80 ). However, because of high O 2 consumption by leukemic blasts and despite an important extracellular O 2 supply, intracellular hypoxia is elevated.…”
Section: Leukemic B Cell Nichesmentioning
confidence: 99%